Investigation of Low-Cost Surface Processing Techniques for Large-Size Multicrystalline Silicon Solar Cells - Yuang-Tung Cheng; Jyh-Jier Ho; William J. Lee; Song-Yeu Tsai; Yung-An Lu; Jia-Jhe Liou; Shun-Hsyung Chang; Kang L. Wang (International Journal of Photoenergy)
The subject of the present work is to develop a simple and effective method of enhancing conversion efficiency in large-size solar cells using multicrystalline silicon (mc-Si) wafer. In this work, industrial-type mc-Si solar cells with area of 125×125 mm2 were acid etched to produce simultaneously POCl3 emitters and silicon nitride deposition by plasma-enhanced chemical vapor deposited (PECVD). The study of surface morphology and reflectivity of different mc-Si etched surfaces has also been discussed in this research. Using our optimal acid etching solution ratio, we are able to fabricate mc-Si solar cells of 16.34% conversion efficiency with double layers silicon nitride (Si3N4) coating. From our experiment, we find that depositing double layers silicon nitride coating on mc-Si solar cells can get the optimal performance parameters. Open circuit (Voc) is 616 mV, short circuit current (Jsc) is 34.1 mA/cm2, and minority carrier diffusion length is 474.16 μm. The isotropic texturing and silicon nitride layers coating approach contribute to lowering cost and achieving high efficiency in mass production.